Ukraine’s Museum of Anti-Terrorist Operation - Polese, A. (Социология: теория, методы, маркетинг, 2018)
The AT0 museum, which opened its doors to the public in May 2016, is indisputably something more than mere chronicles of an armed conflict in Ukraine’s eastern borderlands. Well, like other military museums, it skilfully recreates a battlefield atmosphere. The museum celebrates the bravery of Ukrainian soldiers fighting against the enemy — the terrorists who are encroaching on their homeland. It also draws attention to the sufferings of civilians, who suddenly became victims of Putin’s hybrid war. Yet, that is not all. Another aspect that comes to the fore (albeit it is not stated directly) is the museum’s role in boosting Ukrainian national identity. The “anti-terrorist narrative”, as the author puts it, may be a unique tool for unifying Ukrainian nation. Quite often, a common enemy overrides linguistic or cultural differences: it makes people feel united around the most basic of human needs — survival.